1998
DOI: 10.1046/j.1529-8817.1998.340113.x
|View full text |Cite
|
Sign up to set email alerts
|

ROLE OF PROLINE ACCUMULATION IN RESPONSE TO TOXIC COPPER IN CHLORELLA SP. (CHLOROPHYCEAE) CELLS

Abstract: The green alga Chlorella sp. (strain 2350) was found to accumulate proline, up to a maximum of 0.027 fmol·cell Ϫ1 , under stressful concentrations of cupric ions. The function of the accumulated proline was studied with respect to its effect on copper (Cu) uptake. By induction with salt stress, cells with various levels of intracellular proline were used for this study. It is shown that the amount of Cu taken up by the cells was reduced when the intracellular proline levels were enhanced. When proline was exog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
31
1
1

Year Published

1999
1999
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(39 citation statements)
references
References 30 publications
6
31
1
1
Order By: Relevance
“…The hierarchy of metal toxicity in the present study was similar to that reported previously (Rai et al, 1981 ;De Filippis & Pallaghy, 1994). Metal-induced enhancement of the concentration of intracellular proline in C. vulgaris agreed with reports on higher plants (Alia & Pardha Saradhi, 1993 ;Bassi & Sharma, 1993a,b ;Costa & Morel, 1994), algae (Chang, 1991 ;Wu et al, 1998) and cyanobacteria (Wu et al, 1995). Proline accumulation was highest in cells treated with Cu and Cr, followed in decreasing order by Ni-and Zn-treated cells.…”
Section: supporting
confidence: 88%
See 2 more Smart Citations
“…The hierarchy of metal toxicity in the present study was similar to that reported previously (Rai et al, 1981 ;De Filippis & Pallaghy, 1994). Metal-induced enhancement of the concentration of intracellular proline in C. vulgaris agreed with reports on higher plants (Alia & Pardha Saradhi, 1993 ;Bassi & Sharma, 1993a,b ;Costa & Morel, 1994), algae (Chang, 1991 ;Wu et al, 1998) and cyanobacteria (Wu et al, 1995). Proline accumulation was highest in cells treated with Cu and Cr, followed in decreasing order by Ni-and Zn-treated cells.…”
Section: supporting
confidence: 88%
“…Wu et al (1995) showed that Cu-induced efflux of K + in Anacystis nidulans was minimized in the presence of proline, suggesting that proline possibly protected the plasma membrane from Cu toxicity, or that it perhaps complexed Cu# + thereby decreasing the concentration of free Cu# + in the external environment. In a subsequent paper, Wu et al (1998) demonstrated reduced Cu uptake by cells containing high concentrations of proline, suggesting that proline stabilized the plasma membrane and also reduced the uptake of Cu by algal cells. The present work is not in agreement with those findings, since proline-pretreatment, instead of reducing, caused a slight enhancement (12 %) of Cu uptake in C. vulgaris.…”
Section: mentioning
confidence: 90%
See 1 more Smart Citation
“…Proline accumulated when different algae were exposed to metals such as Cu in Anacystis nidulans, 128 Chlorella sp. 129 and Chlorella vulgaris.…”
Section: Effect Of Exogenous Proline On Plants Exposed To Heavy Metalmentioning
confidence: 99%
“…High level of endogenous proline and lower Cu content in the 1014 line rosettes resulted in better growth regeneration capacities in the presence of 10 lM Cu. In this context, suggestions have been made that proline provides protection by (a) maintaining the water balance, (b) chelating Cu in cytoplasm, or (c) reducing metal uptake (Wu et al 1998). Decline in proline content in the 1014 line grown in the presence of 100 lM Cu for 24 weeks may indicate that a certain threshold of intracellular Cu was crossed, or antioxidative systems were unable to cope with the oxidative stress induced by Cu excess.…”
Section: Effect Of Cu On Proline Contentmentioning
confidence: 99%